Influence of Socio- Economic Factors on Uptake of Maternal Health Services among Reproductive Age Women in Offa Town, Kwara State - Oniyangi, S. O.; Alaro, M. F. (NIU Journal of Social Sciences, 2018)
The study investigated Influence of Socio- economic factors on uptake of maternal health services among reproductive age women in Offa town. In developing countries Socio- economic factors has been identified as major factors that influence the uptake of maternal health services among reproductive age women. The objectives of this study were to: (i) examine the influence of education on the uptake of maternal health services. (ii) determine the influence of economic status on the uptake of maternal health service. (iii) investigate the influence of occupational status on the uptake of maternal health services in  Offa town  kwara, Nigeria.  A descriptive research design of survey type was employed for the study. The Population for the study comprised all registered pregnant women attending antenatal clinic in primary health care centre Offa town. A multistage sampling technique of simple random sampling technique, purposive and proportionate sampling techniques to select 400 respondents. Researcher structured a likert format rating scale questionnaire tagged Influence of Socio-economic factors on uptake of maternal health service. The instrument   was validated by three experts from the Department of Health Promotion and Environmental Health Education, University of Ilorin. A reliability correlation co-efficient of 0.68r was obtained using pearsons product moment correlation statistical tools. Data was collected by the researcher and two trained research assistants. The three research questions and correspondence hypotheses were raised and formulated to guide the study. Inferential statistics of chi-square (x 2 ) was  used to analyze the postulated hypotheses at 0.05 alpha level. The findings of the study showed that: Level of education of reproductive age women have significantly influence on uptake of maternal health services with calculated chi-square (x 2 ) value of (307.07) > critical(x 2 ) value of (21.03 ). Economic status of reproductive age women significant influence the uptake of maternal health services in Offa town because calculated (x 2 ) value 222.90 > critical (x 2 ) value (21.026 ). Occupational status of reproductive age women significant influence the uptake of maternal health services because calculated (x 2 ) value 77.54 > critical value (21.03). The study concluded that level of education, economic and occupation adversely influence the uptake of maternal health services. Therefore it was recommended that efforts should be made toward empowering women through formal education to equip them with the necessary skills to earn and control income .This would help increase the autonomy of women in seeking to issues regarding their own health as many respondents attributed the non-use of the services to financial reasons. Women could also be trained to take up other vocations to supplement their incomes as the general levels of incomes disclosed were low. Furthermore there is also need for government to put in more effort in community health financing in order to improve the health standard of the women of low economic status.